Hard carbon material and preparation method and application thereof

By carbonizing, pore-making and synergistic coating of biomass-based hard carbon materials, the problems of low sodium storage capacity and low first-time Coulomb efficiency in the prior art are solved, and a high-capacity and low-cost hard carbon negative electrode material of sodium ion battery are realized.

CN119601644AActive Publication Date: 2025-03-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD

Patent Information

Application Number
CN202510138334.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-11
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

Existing biomass-based hard carbon materials have problems with low sodium storage capacity and low first-time Coulomb efficiency in sodium ion batteries.

Method used

By carbonizing the biomass raw material in the first inert atmosphere, a hard carbon precursor is obtained, and pore-forming treatment is performed under the action of a pore-forming agent to obtain a pore-hard carbon precursor with a specific surface area of ​​300 to 900 m2/g. Subsequently, two sintering treatments were performed, and coated with a carbon source and a carbon nitrogen source compound to form a hard carbon material with excellent electrochemical properties.

Benefits of technology

The sodium storage capacity and first-time Coulomb efficiency of hard carbon materials are improved, and its reversible capacity, rate performance and cycling performance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601644A_ABST
    Figure CN119601644A_ABST
Patent Text Reader

Abstract

The invention provides a hard carbon material and a preparation method and application thereof, in a Raman spectrum of the hard carbon material, the ratio of the peak intensity at the wavelength of 1345 cm <-1 > to the peak intensity at the wavelength of 1600 cm <-1 > is 0.9-1.3, and the powder impedance of the hard carbon material under the pressure of 16-20 MPa is 0.02-0.07 omega.cm. According to the invention, the reversible specific capacity, the first coulombic efficiency and the rate capability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to negative electrode materials, and in particular to a hard carbon material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries can be widely used in scenarios such as electric two-wheeled vehicles, low-speed electric vehicles, and energy storage systems. At present, the bottleneck of the industrialization of sodium-ion batteries lies mainly in hard carbon negative electrode materials, including the high price of hard carbon, insufficient production capacity, and low industry maturity. Therefore, it is urgent to develop high-capacity and low-cost hard carbon negative electrode materials for sodium-ion batteries. Biomass-based hard carbon is the first choice for large-scale mass production of hard carbon negative electrodes because of its abundant raw material output, low cost, and high sodium storage capacity.

[0003] However, current biomass-based hard carbon generally has the problems of low sodium storage capacity and low first coulombic efficiency. Summary of the invention

[0004] The invention provides a hard carbon material and a preparation method and application thereof. The hard carbon material has high sodium storage capacity and high first coulomb efficiency.

[0005] The present invention provides a hard carbon material, wherein the Raman spectrum of the hard carbon material has a wavelength of 1345 cm -1 The peak intensity and wavelength at 1600 cm -1 The ratio of the peak intensities at is 0.9-1.3, and the powder impedance of the hard carbon material under a pressure of 16-20 MPa is 0.02-0.07 Ω·cm.

[0006] Optionally, the interlayer spacing d of the (002) crystal plane of the hard carbon material is 002 is 0.37~0.40nm; and / or, the hard carbon material includes graphite crystals and amorphous carbon, the width La of the graphite crystals along the a-axis direction is 1.4~2.0nm, and the thickness Lc along the c-axis direction is 0.7~1.0nm; the number of stacking layers is 2.9~3.5.

[0007] Optionally, the hard carbon material includes a core, a first coating layer located on a surface of the core, and a second coating layer located on a surface of the first coating layer, the first coating layer includes carbon elements, and the second coating layer includes nitrogen elements and carbon elements.

[0008] Optionally, the ratio of the number of atoms of the nitrogen element to the number of atoms in the hard carbon material is 0.1% to 2.0%; and / or the sum of the thicknesses of the first coating layer and the second coating layer is 5 to 100 nm.

[0009] Optionally, the porosity of the hard carbon material is 1% to 10%; and / or the specific surface area of ​​the hard carbon material is 0.5 to 20 m 2 / g.

[0010] The present invention provides a method for preparing the hard carbon material as described above, comprising: carbonizing a biomass raw material in a first inert atmosphere to obtain a hard carbon precursor; subjecting the hard carbon precursor to a pore-forming treatment under the action of a pore-forming agent to obtain a hard carbon precursor having a specific surface area of ​​300 to 900 m 2 / g of a porous hard carbon precursor; after mixing the porous hard carbon precursor and a first coating agent, performing a first sintering treatment in a second inert atmosphere to obtain a coated porous hard carbon precursor, wherein the first coating agent includes a carbon source; after mixing the coated porous hard carbon precursor and a second coating agent, performing a second sintering treatment in a third inert atmosphere to obtain the hard carbon material, wherein the second coating agent includes a carbon-nitrogen source compound, and the carbon-nitrogen source compound includes an amine group and an alkyl group.

[0011] Optionally, the biomass raw material includes one or more of glucose, sucrose, starch, coconut shell, walnut shell, hazelnut shell, and wood; and / or, in the process of carbonizing the biomass raw material to obtain a hard carbon precursor, the carbonization temperature is 300~800℃, the carbonization time is 1~10h, and the heating rate is 0.5~3℃ / min; and / or, the process of carbonizing the biomass raw material to obtain a hard carbon precursor also includes: after carbonizing the biomass raw material, crushing and sieving to obtain the hard carbon precursor with a mesh size of 300~500 mesh; and / or, the pore former includes a physical pore former, the physical pore former includes water vapor and / or carbon dioxide, and the temperature of the pore forming treatment is 650~950℃; and / or, the pore former includes a chemical pore former, the chemical pore former includes one or more of potassium hydroxide, sodium hydroxide, zinc chloride, and phosphoric acid, and the temperature of the pore forming treatment is 500~900℃.

[0012] Optionally, the carbon source includes asphalt and / or resin; and / or, the temperature of the first sintering treatment is 1100~1500℃, the holding time is 1~8h, and the heating rate is 0.5~3℃ / min; and / or, the temperature of the second sintering treatment is 700~950℃; and / or, the carbon-nitrogen source compound also includes a carboxyl group, and the carbon-nitrogen source compound includes one or more of isoleucine, leucine, alanine, glycine, proline, valine, tyrosine, phenylalanine, tryptophan, serine, threonine, cysteine, asparagine, glutamine, aspartic acid, glutamic acid, lysine, and arginine; and / or, during the second sintering treatment, the heating rate is 0.5~3℃ / min, and the holding time is 2~6h.

[0013] The present invention provides a negative electrode sheet, which comprises a negative electrode active material layer, wherein the negative electrode active material layer comprises the hard carbon material as described above or the hard carbon material prepared according to the preparation method of the hard carbon material as described above.

[0014] The present invention provides a battery, comprising the negative electrode sheet as described above.

[0015] The present invention provides a hard carbon material and a preparation method and application thereof, which has a large number of active ion storage active sites (such as sodium storage active sites) and the hard carbon material has a low powder impedance, thereby helping to improve the reversible capacity, first coulombic efficiency, rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0017] Figure 1 This is a scanning electron microscope (SEM) photograph of the hard carbon material prepared in Example 1;

[0018] Figure 2 A scanning electron microscope (SEM) photograph of the hard carbon material prepared in Comparative Example 1;

[0019] Figure 3 is an X-ray diffraction (XRD) pattern of the hard carbon material prepared in Example 1;

[0020] Figure 4 Raman spectrum (Raman) of the hard carbon material prepared in Example 1;

[0021] Figure 5 This is the charge and discharge curve of the hard carbon material prepared in Example 1. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0023] In the existing technology, biomass-based hard carbon generally has the problems of low sodium storage capacity and low first coulomb efficiency.

[0024] In order to overcome the defects in the prior art, the present invention provides a hard carbon material (hard carbon negative electrode material) in which the Raman spectrum of the hard carbon material has a wavelength of 1345 cm -1The peak intensity and wavelength at 1600 cm -1 The ratio of the peak intensities at is 0.9~1.3, and the powder impedance of the hard carbon material under a pressure of 16~20MPa is 0.02~0.07Ω·cm.

[0025] According to research and analysis: In the Raman spectrum of the above hard carbon materials, at a wavelength of 1345cm -1 and 1600cm -1 There are characteristic peaks at both ends (D peak and G peak), and the wavelength is 1345cm -1 The peak intensity I D and wavelength of 1600cm -1 The peak intensity I G The ratio of (I D / I G ) is 0.9~1.3, which improves the structure of the hard carbon material, makes the hard carbon material have more active sites for storing active ions (such as sodium storage active sites), and the hard carbon material also has lower powder impedance, which helps to improve the reversible capacity, first coulombic efficiency, rate performance and cycle performance.

[0026] It can be understood that in the Raman spectrum of the hard carbon material, at a wavelength of 1345 cm -1 and 1600cm -1 There are characteristic peaks (D peak and G peak) at both locations, corresponding to the amorphous carbon structure and the graphite-like microcrystalline structure, respectively, that is, the hard carbon material includes amorphous carbon and graphite-like microcrystals. The embodiment of the present invention regulates the structure of amorphous carbon and graphite-like microcrystals in the hard carbon material, so that the hard carbon material has excellent reversible specific capacity and high coulombic efficiency.

[0027] For example, the wavelength is 1345 cm -1 The peak intensity I D and wavelength of 1600cm -1 The peak intensity I G The ratio of (I D / I G ) can be 0.9, 1.0, 1.1, 1.2, 1.3 or a range consisting of any two of them.

[0028] For example, the powder impedance of the hard carbon material under a pressure of 16-20 MPa may be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07 Ω·cm, or a range consisting of any two thereof.

[0029] In some embodiments, the interlayer spacing d of the (002) crystal plane of the hard carbon material is 002 It is 0.37~0.40nm.

[0030] In some embodiments, the hard carbon material comprises graphite microcrystals and amorphous carbon, wherein the width La(002) of the graphite microcrystals along the a-axis direction is 1.4-2.0 nm, and the thickness Lc along the c-axis direction is 0.7-1.0 nm; the number of stacking layers (N=Lc / d 002 +1) is 2.9~3.5. The hard carbon material has a hard carbon structure composed of short-range ordered graphite-like microcrystals and amorphous carbon with appropriate average width, stacking thickness and stacking layer number, has more sodium (or lithium) storage active sites, and the hard carbon material has low powder impedance, thus showing good electrochemical performance, which is helpful to improve reversible capacity, first coulomb efficiency, rate performance and cycle performance.

[0031] In some embodiments, the hard carbon material includes a core, a first coating layer located on the surface of the core, and a second coating layer located on the surface of the first coating layer, the first coating layer includes carbon elements, and the second coating layer includes nitrogen elements and carbon elements.

[0032] Specifically, the ratio of the number of atoms of the above nitrogen element to the number of atoms in the hard carbon material can be 0.1% to 2.0% (that is, the nitrogen doping ratio in the hard carbon material is 0.1at% to 2.0at%). A small amount of nitrogen doping can increase the defect active sites of the hard carbon material and improve the conductivity, thereby increasing the reversible capacity, increasing the slope region capacity, and improving the rate performance.

[0033] For example, the ratio of the number of atoms of nitrogen to the number of atoms in the hard carbon material may be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, or a range consisting of any two thereof.

[0034] The above-mentioned first coating layer may include carbon elements, and the second coating layer may also include carbon elements. That is, the above-mentioned hard carbon material is coated with nitrogen elements and also includes a soft carbon coating layer. This can avoid the side effect of increased irreversible capacity caused by nitrogen doping, improve the interface of the hard carbon material, reduce the side reaction between the defective surface caused by doping and the electrolyte, and improve the first coulombic efficiency and rate performance of the hard carbon material.

[0035] Furthermore, the sum of the thicknesses of the first coating layer and the second coating layer can be 5 to 100 nm, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100 nm or a range consisting of any two thereof.

[0036] In some embodiments, the porosity of the hard carbon material is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two thereof.

[0037] In some embodiments, the specific surface area of ​​the hard carbon material is 0.5 to 20 m2 / g, for example 0.5, 1, 5, 10, 20 m 2 / g or a range consisting of any two of them.

[0038] The present invention also provides a method for preparing the hard carbon material, comprising: carbonizing a biomass raw material in a first inert atmosphere to obtain a hard carbon precursor; subjecting the hard carbon precursor to pore-forming treatment (pore size control) under the action of a pore-forming agent to obtain a hard carbon precursor with a specific surface area of ​​300 to 900 m 2 / g of a porous hard carbon precursor; after mixing the porous hard carbon precursor and the first coating agent, performing a first sintering treatment in a second inert atmosphere to obtain a coated porous hard carbon precursor, wherein the first coating agent includes a carbon source; after mixing the coated porous hard carbon precursor and the second coating agent, performing a second sintering treatment in a third inert atmosphere to obtain a hard carbon material, wherein the second coating agent includes a carbon-nitrogen source compound, and the carbon-nitrogen source compound includes an amine group and an alkyl group.

[0039] According to research analysis: Pore-making treatment helps to inhibit graphite microcrystallization during the carbonization process of biomass raw materials, and helps to produce hard carbon materials including graphite-like microcrystals and amorphous carbon, and the hard carbon material is coated with two layers, wherein the second layer of coating adopts carbon-nitrogen synergistic coating. On the one hand, nitrogen doping can enhance the defect active sites of hard carbon materials and enhance the conductivity, thereby enhancing the reversible capacity, increasing the slope zone capacity, and improving the rate performance. On the other hand, carbon-nitrogen synergistic coating can avoid the side effect of increased irreversible capacity caused by nitrogen doping, improve the interface of hard carbon materials, reduce the side reaction between the defective surface caused by doping and the electrolyte, and enhance the first coulombic efficiency and rate performance of hard carbon materials.

[0040] Specifically, biomass raw materials may include one or more of glucose, sucrose, starch, coconut shells, walnut shells, hazelnut shells, and wood, and have the advantages of abundant raw material output, low cost, and high sodium (or lithium) storage capacity.

[0041] In the process of carbonizing the biomass raw material (low-temperature pyrolysis carbonization) to obtain the hard carbon precursor, the carbonization temperature can be 300-800° C. and the carbonization time (insulation time) can be 1-10 hours.

[0042] In addition, the heating rate during the carbonization process can be 0.5-3°C / min.

[0043] In a specific implementation, the above-mentioned process of carbonizing the biomass raw material to obtain the hard carbon precursor also includes: after carbonizing the biomass raw material, a carbonized material is obtained, and then the carbonized material is crushed and sieved (for example, crushed, classified and sieved). The equipment used in the above-mentioned crushing process may include an air flow crushing and classifying machine, and the mesh number of the sieve can be 300-500 meshes. The specific surface area of ​​the obtained hard carbon precursor is generally less than 300 m2 / g, for example, the ratio is about 10~250m 2 / g, and the hard carbon precursor with a particle size of about 4~15µm is beneficial to the uniformity and sufficiency of subsequent sintering and doping coating reactions.

[0044] More specifically, for example, a jet mill classifier is used to obtain carbonized material at a frequency of 40 Hz for the air crusher and 40 Hz for the classifier, and then sieved with a sieve mesh of 325 to obtain a hard carbon precursor with a particle size of about 4-6 μm. This particle size is conducive to the uniformity and sufficiency of subsequent sintering and doping and coating reactions, and there is no need for secondary crushing and classification, only sieving is required; the specific surface area of ​​the hard carbon precursor is generally less than 300 m 2 / g, for example 10~250m 2 / g.

[0045] During the high-temperature carbonization process of biomass raw materials (hard carbon raw materials), volatile gases including water vapor, carbon dioxide, and carbon monoxide are released, forming pores inside the hard carbon material, resulting in the hard carbon material having a high porosity and a large specific surface area, causing problems such as low compaction density of hard carbon and low first coulombic efficiency (first-week coulombic efficiency). The pore structure of most hard carbons is naturally formed during the high-temperature carbonization process, and it is difficult to control the pore size structure, resulting in hard carbon often having more open pores. Its open pore structure will lead to consumption of electrolyte and sodium precipitation. Although pore creation will increase the reversible capacity of sodium (or lithium) storage to a certain extent, the first coulombic efficiency will be greatly reduced as the specific surface area of ​​hard carbon increases significantly. There is still a lack of effective methods to control the pore structure of hard carbon. The sodium (or lithium) storage capacity of hard carbon materials needs to be further improved, and there are problems with poor cycle performance and rate performance. In addition, in general, in the structure of sodium storage carbon materials, long-range ordered structures (such as graphite crystallites) can hardly accommodate the embedding of sodium ions. Therefore, long-range ordered structure carbon will reduce the sodium storage active sites, resulting in the loss of reversible capacity.

[0046] Based on the fact that a rich closed-pore structure is the key to improving the reversible storage performance of hard carbon active ions (such as sodium ions or lithium ions), the specific surface area of ​​the porous hard carbon precursor after pore formation treatment is controlled within a range of 300-900 m 2 / g, the graphitization structure of hard carbon is regulated by pore engineering, and the pores of hard carbon precursor are increased by pore-forming treatment. A large number of pores hinder the formation of hard carbon graphite microcrystals, inhibit the tendency of excessive graphite microcrystalization of hard carbon materials, increase the spacing between the (002) crystal planes of the carbon layer, and increase the active sites for sodium (or lithium) storage. The reversible capacity of the porous hard carbon precursor can be increased after high-temperature carbonization, and the structure of graphite microcrystals and amorphous carbon in the hard carbon material is controlled within a suitable range, which is helpful to obtain I D / I GHard carbon materials with a carbon density of 0.9 to 1.3 can take into account both high reversible capacity, first coulombic efficiency and cycle performance.

[0047] For example, the specific surface area of ​​the porous hard carbon precursor may be 300, 350, 400, 450, 500, 600, 700, 800, 900 m 2 / g or a range consisting of any two of them.

[0048] The above-mentioned pore-forming treatment may include a physical pore-forming treatment method or a chemical pore-forming treatment method, which is explained in detail as follows.

[0049] In the physical pore forming treatment method, the pore forming agent includes a physical pore forming agent, and the physical pore forming agent may include water vapor and / or carbon dioxide. Accordingly, the temperature of the pore forming treatment (i.e., the pyrolysis process of the physical pore forming agent) may be 650-950° C., for example, 650, 700, 800, 900, 950° C., or a range consisting of any two thereof.

[0050] More specifically, the physical pore former may also include nitrogen, that is, water vapor and / or a mixture of carbon dioxide and nitrogen is used as the physical pore former.

[0051] In addition, in the specific implementation, the above-mentioned physical pore formers, such as water vapor, carbon dioxide, a mixture of water vapor and / or carbon dioxide and nitrogen, can be introduced into the reaction system at a flow rate of 0.15~0.25L / min, for example, 0.15, 0.2, 0.25L / min or a range composed of any two thereof. In the chemical pore forming treatment method, the above-mentioned pore former includes a chemical pore former, and the chemical pore former can include one or more of potassium hydroxide, sodium hydroxide, zinc chloride (ZnCl2), and phosphoric acid (H3PO4). Accordingly, the temperature of the pore forming treatment (that is, the pyrolysis process of the chemical pore former) can be 500~900°C, for example, 500, 600, 700, 800, 900°C or a range composed of any two thereof.

[0052] In a specific implementation, a solution including a chemical pore former can be prepared first, for example, a solution including one or more of potassium hydroxide, sodium hydroxide, zinc chloride (ZnCl2), and phosphoric acid (H3PO4), and then the hard carbon precursor is immersed in the solution including the chemical pore former, and then dried, and then pyrolyzed at 500-900°C to obtain a hard carbon precursor with a specific surface area of ​​300-900m 2 / g of porous hard carbon precursor.

[0053] The dosage of the above-mentioned pore-forming agent and the pore-forming time can be appropriately adjusted according to the actual situation and the expected specific surface area of ​​the porous hard carbon precursor.

[0054] The conventional coating process generally uses a hard carbon sample after high-temperature sintering, and after coating the mixture, a secondary high-temperature carbonization is performed. The above conventional coating process generally leads to an increase in defects and an increase in specific surface area, resulting in a decrease in the first coulomb efficiency. In addition, the compaction density of hard carbon prepared from general biomass raw materials is low, and the hard carbon prepared by pore-making technology has a lower compaction density due to the generation of a large number of pore structures. However, in the preparation method of the embodiment of the present invention, the porous hard carbon precursor is coated with the first coating agent and the second coating agent, which can effectively reduce the specific surface area, improve the compaction density of the hard carbon material, reduce the powder impedance, and improve the first coulomb efficiency and rate performance.

[0055] After mixing the porous hard carbon precursor and the first coating agent (for example, using a mixing modifier to perform VC mixing treatment), a first sintering treatment (high-temperature carbonization) is performed in a second inert atmosphere to obtain a coated porous hard carbon precursor. The process can include: mixing the porous hard carbon precursor and the first coating agent (for example, VC mixing treatment), and then performing a first sintering treatment in a second inert atmosphere to obtain a coated porous hard carbon precursor.

[0056] Specifically, in the mixed material obtained by mixing the porous hard carbon precursor and the first coating agent, the mass percentage of the first coating agent (mixing ratio) is 1wt%~10wt%, for example, 1wt%, 3wt%, 5wt%, 7wt%, 9wt%, 10wt% or a range composed of any two of them.

[0057] In addition, the time for mixing the porous hard carbon precursor and the first coating agent may be 15 to 60 minutes, and the stirring speed may be 1000 to 2000 rpm.

[0058] The first coating agent (or the carbon source therein) may include asphalt and / or resin, including but not limited to one or more of petroleum asphalt, coal asphalt, β resin, phenolic resin, and epoxy resin.

[0059] In a specific implementation, the temperature of the first sintering treatment (high temperature carbonization) can be 1100-1500° C., and the holding time can be 1-8 hours.

[0060] In addition, during the first sintering process (high temperature carbonization), the heating rate may be 0.5-3°C / min.

[0061] The traditional heteroatom doping process generally leads to an increase in defects in carbon materials and an increase in specific surface area, resulting in a significant decrease in the first coulombic efficiency of hard carbon; at the same time, the coating and doping processes are difficult to coordinate and the process is complicated.

[0062] In an embodiment of the present invention, the above-mentioned second coating agent includes a carbon-nitrogen source compound, which includes an amine group (-NH2) and an alkyl group (-R). The hard carbon material is modified in a one-step manner by nitrogen doping and carbon coating. The obtained hard carbon material (hard carbon negative electrode material) is doped with nitrogen and contains a soft carbon coating layer. A small amount of nitrogen doping can increase the defective active sites of the hard carbon and improve the conductivity, thereby increasing the reversible capacity, increasing the slope zone capacity, and improving the rate performance. At the same time, the soft carbon coating layer constructed synchronously can avoid the side effect of increased irreversible capacity caused by nitrogen doping, improve the hard carbon interface, reduce the side reaction between the defective surface caused by doping and the electrolyte, and improve the first coulombic efficiency and cycle performance of the hard carbon material (hard carbon negative electrode material).

[0063] Specifically, the carbon-nitrogen source compound may include a carboxyl group, and the carbon-nitrogen source compound includes one or more of isoleucine, leucine, alanine, glycine, proline, valine, tyrosine, phenylalanine, tryptophan, serine, threonine, cysteine, asparagine, glutamine, aspartic acid, glutamic acid, lysine, and arginine.

[0064] Furthermore, the above-mentioned carbon-nitrogen source compound may also include a carboxyl group (-COOH), which helps to undergo a cross-linking reaction with the oxygen-containing functional groups on the surface of the hard carbon material to form cross-linked structures such as ester groups and acid anhydrides, hinder the rearrangement of the hard carbon graphite microcrystalline structure, help increase the sodium storage capacity, and help improve the reversible capacity, first coulomb efficiency, rate performance and cycle performance.

[0065] It is understandable that the temperature of the second sintering treatment should be determined in combination with the specific type of the carbon-nitrogen source compound in order to achieve a better coating effect.

[0066] In some embodiments, the temperature of the second sintering process is 700-950° C., for example, 700, 800, 900, 950° C. or a range consisting of any two thereof.

[0067] In specific implementation, during the above-mentioned second sintering treatment process, the heating rate can be 0.5~3°C / min, for example, 0.5, 1, 2, 3°C / min or a range consisting of any two thereof, and the holding time can be 2~6h, for example, 2, 3, 4, 5, 6h or a range consisting of any two thereof.

[0068] It can be understood that the inert atmosphere (the first inert atmosphere, the second inert atmosphere, and the third inert atmosphere) of the embodiment of the present invention may include one or more of nitrogen, argon, and helium.

[0069] It is understandable that in specific applications, the hard carbon material can be crushed and sieved to facilitate its use in preparing the negative electrode sheet. In the sieving process, the mesh size of the sieve can be 300-500 meshes.

[0070] The hard carbon material can be used to prepare a lithium ion battery negative electrode sheet or a sodium ion battery negative electrode sheet, preferably a sodium ion battery negative electrode sheet, and then used to prepare a lithium ion battery or a sodium ion battery, preferably a sodium ion battery.

[0071] The embodiment of the present invention further provides a negative electrode sheet, which includes a negative electrode active material layer, and the negative electrode active material layer includes the hard carbon material or the hard carbon material prepared according to the preparation method of the hard carbon material. Based on the hard carbon material, the negative electrode sheet has corresponding effects, which will not be described in detail here.

[0072] The embodiment of the present invention further provides a battery, the battery comprising the negative electrode sheet. Based on the negative electrode sheet or the hard carbon material, the battery has corresponding effects, which will not be described in detail here.

[0073] In some embodiments, the battery comprises a sodium ion battery.

[0074] It is understandable that the above-mentioned battery also includes a positive electrode plate, a separator and an electrolyte.

[0075] The positive electrode sheet specifically comprises a positive electrode current collector and a positive electrode active layer arranged on at least one functional surface of the positive electrode current collector, and the positive electrode active layer comprises a positive electrode active material.

[0076] When preparing the positive electrode sheet, for example, the positive electrode active material, the conductive agent and the binder can be dispersed in an appropriate amount of N-methylpyrrolidone (NMP) solvent, and fully stirred and mixed to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, rolling and slitting.

[0077] Among them, the material of the positive electrode current collector can be at least one of aluminum foil and nickel foil; the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, carbon fiber, carbon nanotubes, and conductive graphite; the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, and polyurethane.

[0078] The positive electrode active material may include one or more of layered oxides, polyanion compounds, Prussian blue compounds, sodium peroxides, and sodium superoxides.

[0079] The embodiment of the present invention does not strictly limit the selection of the electrolyte, and may include one or more of the solvents commonly used in the current sodium ion battery electrolyte, and the electrolyte sodium salt commonly used in the current sodium ion electrolyte, for example: the solvent may be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, ethyl methyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, γ-butyrolactone, etc.; the electrolyte may be, for example, one or more of sodium hexafluorophosphate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, and sodium fluorotrifluoromethylsulfonylimide.

[0080] The embodiment of the present invention does not strictly limit the material selection of the diaphragm, and it can be a diaphragm material commonly used in sodium ion batteries, such as a polypropylene diaphragm (PP), a polyethylene diaphragm (PE), a polypropylene / polyethylene double-layer composite film (PP / PE), a polyimide electrospinning diaphragm (PI), a polypropylene / polyethylene / polypropylene three-layer composite film (PP / PE / PP), a cellulose non-woven fabric diaphragm, and a diaphragm with a ceramic coating.

[0081] When preparing sodium-ion batteries, the positive electrode sheet, separator and negative electrode sheet are wound or stacked to obtain a bare cell, and the bare cell is packaged in a pre-stamped aluminum-plastic film bag. After the packaged battery is dried at 85°C, the electrolyte is injected into the dry battery. After the battery is shelved, formed and sealed for the second time, the preparation of the sodium-ion battery is completed.

[0082] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.

[0083] Example 1

[0084] This embodiment provides a method for preparing a hard carbon material (hard carbon negative electrode material) for a sodium ion battery, comprising:

[0085] 1) Carbonize the coconut shell in nitrogen at a temperature of 300°C, a heating rate of 2°C / min, and a carbonization time of 4 hours. Then crush and sieve the coconut shell. The mesh number of the sieve used is 325 meshes to obtain a hard carbon precursor with a particle size of 6µm. The specific surface area of ​​the hard carbon precursor is about 250m 2 / g;

[0086] 2) Carbon dioxide gas was introduced into the hard carbon precursor for pore formation treatment. The pore formation treatment temperature was 800°C, the time was 1 h, the heating rate was 3°C / min, and the flow rate of carbon dioxide gas was 0.2 L / min. The specific surface area was 650 m 2 / g of porous hard carbon precursor;

[0087] 3) At a stirring speed of 1500 rpm, the specific surface area of ​​650 m 2 / g of porous hard carbon precursor and asphalt are mixed, and the mass percentage of asphalt in the mixed material obtained after the porous hard carbon precursor and the asphalt are mixed is 5wt%, and the mixing time is 30min; then a first sintering treatment is performed in nitrogen to obtain a coated porous hard carbon precursor, wherein the temperature of the first sintering treatment is 1300°C, the insulation time is 4h, and the heating rate can be 3°C / min;

[0088] 4) After mixing the coated porous hard carbon precursor and glutamate, a second sintering treatment is carried out in nitrogen. The temperature of the second sintering treatment is 900°C, the heating rate is 2°C / min, and the insulation time is 4 hours; then it is crushed and sieved with a mesh size of 325 to obtain a hard carbon material (hard carbon negative electrode material) with a carbon coating layer (coating layer) having a thickness of 10 nm.

[0089] Example 2

[0090] This embodiment is basically the same as Embodiment 1, except that:

[0091] 1) Replace coconut shell with walnut shell and adjust the carbonization temperature to 400℃;

[0092] 2) Replace asphalt with beta resin;

[0093] 3) Replace glutamate with glycine, and the nitrogen doping ratio (at%) is 2.0 at %;

[0094] 4) adjusting the amount of coating agent so that the thickness of the carbon coating layer (coating layer) is 5 nm;

[0095] Other conditions remain unchanged.

[0096] Example 3

[0097] This embodiment is basically the same as Embodiment 1, except that:

[0098] 1) The carbonization temperature is adjusted to 800°C;

[0099] 2) Step 2) is adjusted to mix the hard carbon precursor and potassium hydroxide in a mass ratio of 1:1, and then perform pore formation treatment (pyrolysis) at 800°C, with a heating rate of 3°C / min and a reaction time of 2h to obtain a porous hard carbon precursor;

[0100] 3) adjusting the amount of coating agent so that the thickness of the carbon coating layer (coating layer) is 100 nm;

[0101] Other conditions remain unchanged.

[0102] Example 4

[0103] This embodiment is basically the same as Embodiment 1, except that:

[0104] In step 1), coconut shell was replaced by glucose, the carbonization time was adjusted to 10 h, the heating rate was adjusted to 0.5°C / min, and the mesh size of the sieve used for sieving was 300 mesh; other conditions remained unchanged.

[0105] Example 5

[0106] This embodiment is basically the same as Embodiment 1, except that:

[0107] In step 1), coconut shell was replaced by starch, the carbonization time was adjusted to 1 h, the heating rate was adjusted to 3 °C / min, and the mesh size of the sieve used for sieving was 500 mesh; other conditions remained unchanged.

[0108] Example 6

[0109] This embodiment is basically the same as Embodiment 1, except that:

[0110] In step 2), carbon dioxide is replaced by water vapor, and the pore-forming treatment temperature is adjusted to 650°C. After the pore-forming treatment, the specific surface area is 300m 2 / g of porous hard carbon precursor; other conditions remain unchanged.

[0111] Example 7

[0112] This embodiment is basically the same as Embodiment 1, except that:

[0113] In step 2), the carbon dioxide was replaced by a mixture of carbon dioxide and nitrogen (volume ratio of 1:3), and the pore-forming treatment temperature was adjusted to 950°C. After the pore-forming treatment, the specific surface area was 900m 2 / g of porous hard carbon precursor; other conditions remain unchanged.

[0114] Example 8

[0115] This embodiment is basically the same as Embodiment 3, except that:

[0116] In step 2), zinc chloride is used to replace potassium hydroxide, and the pore-forming treatment temperature is 500° C.; other conditions remain unchanged.

[0117] Example 9

[0118] This embodiment is basically the same as Embodiment 3, except that:

[0119] In step 2), phosphoric acid is used to replace potassium hydroxide, and the pore-forming treatment temperature is 900° C.; other conditions remain unchanged.

[0120] Example 10

[0121] This embodiment is basically the same as Embodiment 1, except that:

[0122] In step 3), the temperature of the first sintering treatment is 1100°C, the holding time is 8h, and the heating rate is 0.5°C / min;

[0123] In step 4), glutamate is replaced by phenylalanine, the temperature of the second sintering treatment is 950°C, the heating rate is 0.5°C / min, and the holding time is 6h.

[0124] Embodiment 11

[0125] This embodiment is basically the same as Embodiment 1, except that:

[0126] In step 3), the temperature of the first sintering treatment is 1500°C, the holding time is 1h, and the heating rate is 3°C / min;

[0127] In step 4), glutamate is replaced by proline, the temperature of the second sintering treatment is 700°C, the heating rate is 3°C / min, and the holding time is 2h.

[0128] Comparative Example 1

[0129] This comparative example is basically the same as Example 1, except that:

[0130] No pore-making or coating treatment is performed; other conditions remain unchanged.

[0131] This comparative example provides a method for preparing a sodium ion battery hard carbon material (hard carbon negative electrode material), comprising:

[0132] 1) Carbonize the coconut shell in nitrogen at a temperature of 300°C, a heating rate of 2°C / min, and a carbonization time of 4 hours. Then crush and sieve the coconut shell. The mesh number of the sieve used is 325 meshes to obtain a hard carbon precursor with a particle size of 6µm. The specific surface area of ​​the hard carbon precursor is about 250m 2 / g;

[0133] 2) Then, a first sintering treatment is carried out in nitrogen, followed by crushing and sieving, the mesh size of the sieve is 325 mesh, to obtain a hard carbon material (hard carbon negative electrode material), wherein the temperature of the first sintering treatment is 1300°C, the insulation time is 4h, and the heating rate can be 3°C / min.

[0134] Comparative Example 2

[0135] This comparative example is basically the same as Example 1, except that:

[0136] No coating treatment was performed; other conditions remained unchanged.

[0137] This comparative example provides a method for preparing a sodium ion battery hard carbon material (hard carbon negative electrode material), comprising:

[0138] 1) Carbonize the coconut shell in nitrogen at a temperature of 300°C, a heating rate of 2°C / min, and a carbonization time of 4 hours. Then crush and sieve the coconut shell. The mesh number of the sieve used is 325 meshes to obtain a hard carbon precursor with a particle size of 6µm. The specific surface area of ​​the hard carbon precursor is about 250m 2 / g;

[0139] 2) Carbon dioxide gas was introduced into the hard carbon precursor for pore formation treatment. The pore formation treatment temperature was 800°C, the time was 1 h, the heating rate was 3°C / min, and the flow rate of carbon dioxide gas was 0.2 L / min. The specific surface area was 650 m 2 / g of porous hard carbon precursor;

[0140] 3) Then, a first sintering treatment is carried out in nitrogen, followed by crushing and sieving, the mesh size of the sieve is 325 mesh, to obtain a hard carbon material (hard carbon negative electrode material), wherein the temperature of the first sintering treatment is 1300°C, the insulation time is 4h, and the heating rate can be 3°C / min.

[0141] Comparative Example 3

[0142] This comparative example is basically the same as Example 1, except that:

[0143] No pore-forming treatment was performed; other conditions remained unchanged.

[0144] This comparative example provides a method for preparing a sodium ion battery hard carbon material (hard carbon negative electrode material), comprising:

[0145] 1) Carbonize the coconut shell in nitrogen at a temperature of 300°C, a heating rate of 2°C / min, and a carbonization time of 4 hours. Then crush and sieve the coconut shell. The mesh number of the sieve used is 325 meshes to obtain a hard carbon precursor with a particle size of 6µm. The specific surface area of ​​the hard carbon precursor is about 250m2 / g;

[0146] 2) Mixing the hard carbon precursor and asphalt at a stirring speed of 1500 rpm, wherein the mass percentage of asphalt (mixing ratio) in the mixture obtained by mixing the hard carbon precursor and asphalt is 5wt%, and the mixing time is 30 minutes; then performing a first sintering treatment in nitrogen to obtain a coated porous hard carbon precursor, wherein the temperature of the first sintering treatment is 1300°C, the holding time is 4 hours, and the heating rate can be 3°C / min;

[0147] 3) After mixing the coated porous hard carbon precursor and glutamate, a second sintering treatment is carried out in nitrogen. The temperature of the second sintering treatment is 900°C, the heating rate is 2°C / min, the insulation time is 4h, and the nitrogen doping ratio (at%) is 0.5%. Then, the mixture is crushed and sieved with a mesh size of 325 to obtain a hard carbon material (hard carbon negative electrode material).

[0148] Comparative Example 4

[0149] This comparative example is basically the same as Example 1, except that:

[0150] No nitrogen-carbon synergistic coating treatment was performed; other conditions remained unchanged.

[0151] This comparative example provides a method for preparing a sodium ion battery hard carbon material (hard carbon negative electrode material), comprising:

[0152] 1) Carbonize the coconut shell in nitrogen at a temperature of 300°C, a heating rate of 2°C / min, and a carbonization time of 4 hours. Then crush and sieve the coconut shell. The mesh number of the sieve used is 325 meshes to obtain a hard carbon precursor with a particle size of 6µm. The specific surface area of ​​the hard carbon precursor is about 250m 2 / g;

[0153] 2) Carbon dioxide gas was introduced into the hard carbon precursor for pore formation treatment. The pore formation treatment temperature was 800°C, the time was 1 h, the heating rate was 3°C / min, and the flow rate of carbon dioxide gas was 0.2 L / min. The specific surface area was 650 m 2 / g of porous hard carbon precursor;

[0154] 3) At a stirring speed of 1500 rpm, the specific surface area of ​​650 m 2 / g of porous hard carbon precursor and asphalt are mixed, and the mass percentage of asphalt in the mixed material obtained after the porous hard carbon precursor and the asphalt are mixed is 5wt%, and the mixing time is 30min; then a first sintering treatment is performed in nitrogen to obtain a coated porous hard carbon precursor, wherein the temperature of the first sintering treatment is 1300°C, the insulation time is 4h, and the heating rate can be 3°C / min;

[0155] 4) Then it is crushed and sieved, the mesh size of the sieve is 325 meshes, and a hard carbon material (hard carbon negative electrode material) is obtained.

[0156] Comparative Example 5

[0157] This comparative example is basically the same as Example 1, except that:

[0158] In step 2), during the pore-forming treatment, the time of pore-forming treatment and the amount of pore-forming agent are adjusted to obtain a specific surface area of ​​250 m 2 / g of porous hard carbon precursor; other conditions remain unchanged.

[0159] Comparative Example 6

[0160] This comparative example is basically the same as Example 1, except that:

[0161] In step 2), during the pore-forming treatment, the time of pore-forming treatment and the amount of pore-forming agent were adjusted to obtain a specific surface area of ​​950 m 2 / g of porous hard carbon precursor; other conditions remain unchanged.

[0162] Comparative Example 7

[0163] This comparative example is basically the same as Example 1, except that:

[0164] In step 4), the temperature of the second sintering treatment is adjusted to 650° C.; other conditions remain unchanged.

[0165] Comparative Example 8

[0166] This comparative example is basically the same as Example 1, except that:

[0167] The temperature of the second sintering treatment in step 4) is adjusted to 1000°C; other conditions remain unchanged.

[0168] Test example

[0169] 1. The following parameters of the hard carbon materials of each embodiment and comparative example were tested:

[0170] 1) Scanning electron microscope (SEM) test: SEM images were obtained using a Hitachi Regulus 8100 / SU 8010 scanning electron microscope;

[0171] 2) X-ray diffraction (XRD): XRD is tested by X-ray powder diffractometer, and the (002) crystal plane spacing d is calculated. 002 , the average width La of graphite crystallites along the a-axis, the thickness Lc of the stacking along the c-axis, and the number of stacking layers N, where d 002 =λ / (2sinθ); La=1.84λ / (βcosθ); Lc=0.9λ / (βcosθ); N=Lc / d 002 +1, where λ is the wavelength of X-rays, β is the half-height width of the (002) crystal plane, and θ is the diffraction angle of the (002) crystal plane;

[0172] 3) Raman test: Raman spectrum is obtained by laser confocal Raman spectrometer, and I is calculated based on the intensity ratio of D peak and G peak in Raman spectrum. D / I G The value of

[0173] 4) X-ray photoelectron spectroscopy (XPS): The nitrogen doping ratio is obtained by X-ray photoelectron spectrometer testing;

[0174] 5) The thickness of the carbon coating layer is tested by transmission electron microscopy (TEM), and the thickness of the carbon coating layer is measured in high-resolution transmission electron microscopy photos;

[0175] 6) Cross-section porosity: Cross-section porosity is obtained by taking a SEM photo of the material cross section and then analyzing it using the OPTON software;

[0176] 7) Specific surface area (BET): BET is measured using Bester 3H-2000BET-A according to the national standard GB / T 19587-2017;

[0177] 8) Impedance (powder impedance): measured using the four-probe method in accordance with the national standard GB / T 30835-2014.

[0178] 2. The above-mentioned hard carbon materials are respectively used to make negative electrode sheets and assembled into CR2032 button batteries. The method for assembling CR2032 batteries is as follows: the hard carbon material (hard carbon negative electrode material) is placed in a slurry mixer with a mass ratio of 80:10:10, and then nitrogen methyl pyrrolidone solvent is added and mixed evenly to obtain a slurry, and the slurry is evenly coated on the surface of the carbon-coated aluminum foil and placed in a vacuum drying oven at 100°C for 12 hours. At the same time, a CR2032 battery is assembled using metallic sodium as a counter electrode, glass fiber as a diaphragm, and a 1 mol / L sodium hexafluorophosphate (NaPF6) ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1) mixed solution as an electrolyte.

[0179] The button cell was subjected to constant current charge and discharge test at 25°C on a Xinwei multi-channel test system, with a voltage of 0-2.0V, a rate of 0.1C, and 1C=300mA / g.

[0180] Reversible capacity: Discharge to 0V at a constant current of 0.1C rate, the discharge capacity obtained is the first discharge capacity, then charge to 2V at a constant current of 0.1C, the charge capacity obtained is the first charge capacity, the first charge capacity is the reversible capacity;

[0181] First coulombic efficiency: the percentage obtained by dividing the first charge capacity by the first discharge capacity;

[0182] 1C cycle 50 cycle capacity retention rate: the percentage obtained by dividing the charging capacity of the 50th cycle at 1C rate by the charging capacity of the first cycle;

[0183] 2C capacity retention rate: The percentage obtained by dividing the charge capacity obtained at a 2C rate by the reversible capacity.

[0184] Test results:

[0185] Table 1

[0186]

[0187] Data analysis: As can be seen from the above table, each embodiment, through pore creation (pore size control) and coordinated nitrogen-carbon synergistic coating, helps to obtain a wavelength of 1345cm in the Raman spectrum. -1 The peak intensity I D and wavelength of 1600cm -1 The peak intensity I G The ratio of (I D / I G ) is 0.9~1.3 and the powder impedance is low.

[0188] Table 2

[0189]

[0190] Data analysis: It can be seen from Table 1 and Table 2 that, compared with the comparative example, the hard carbon in the embodiment of the present invention contains a composite carbon structure of amorphous carbon and graphite-like microcrystals and has a suitable Raman spectrum peak intensity ratio I D / I G (0.9~1.3), so there are more sodium storage active sites, which makes the hard carbon material have excellent reversible specific capacity and high coulombic efficiency. At the same time, in the embodiment, by regulating the pores of the precursor and then nitrogen doping and carbon layer coating, a hard carbon material with a suitable Raman spectrum peak intensity ratio (0.9~1.3), a large interlayer spacing (0.37~0.40nm) and a low powder impedance (0.02~0.07Ω·cm) is obtained, which helps to improve the reversible capacity, first coulombic efficiency, rate performance and cycle performance of the hard carbon material.

[0191] Figure 1 and Figure 2 The scanning electron microscope images of the hard carbon materials prepared in Example 1 and Comparative Example 1 respectively show that both of them have blocky morphology. Figure 1 The particle size is slightly larger, and there is a wrinkled coating layer on the surface, which proves that the hard carbon material prepared in Example 1 has a surface coating modification effect compared with Comparative Example 1;

[0192] from Figure 3 The X-ray diffraction pattern of the hard carbon material prepared in Example 1 shows two characteristic bulge peaks of typical hard carbon materials, corresponding to the (002) and (100) crystal planes, respectively. The (002) crystal plane spacing d is calculated to be 002 The average width La of graphite crystallites along the a-axis and the thickness Lc of the graphite crystallites along the c-axis are 1.48 nm and 0.72 nm, respectively, and the number of stacking layers N is 2.9.

[0193] according to Figure 4 The Raman spectrum of the hard carbon material prepared in Example 1 can be calculated to have a wavelength of 1345 cm -1 The D peak intensity at I D and wavelength of 1600cm -1 The G peak intensity at I G The ratio of (I D / I G ) is 1.1;

[0194] from Figure 5 From the charge and discharge curve of the hard carbon material prepared in Example 1, it can be concluded that the material exhibits excellent sodium storage performance, with a reversible specific capacity of 337 mAh / g and a first coulombic efficiency of 92%.

[0195] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hard carbon material, characterized in that: In the Raman spectrum of the hard carbon material, the wavelength is 1345 cm -1 The peak intensity and wavelength at 1600 cm -1 The ratio of the peak intensities at is 0.9-1.3, and the powder impedance of the hard carbon material under a pressure of 16-20 MPa is 0.02-0.07 Ω·cm.

2. The hard carbon material according to claim 1, characterized in that The interlayer spacing d of the (002) crystal plane of the hard carbon material 002 0.37~0.40nm; And / or, the hard carbon material includes graphite crystals and amorphous carbon, the width La of the graphite crystals along the a-axis direction is 1.4~2.0nm, the thickness Lc along the c-axis direction is 0.7~1.0nm; the number of stacking layers is 2.9~3.

5.

3. The hard carbon material according to claim 1 or 2, characterized in that The hard carbon material includes a core, a first coating layer located on a surface of the core, and a second coating layer located on a surface of the first coating layer, wherein the first coating layer includes carbon elements, and the second coating layer includes nitrogen elements and carbon elements.

4. The hard carbon material according to claim 3, characterized in that The ratio of the number of atoms of the nitrogen element to the number of atoms in the hard carbon material is 0.1% to 2.0%; And / or, the sum of the thicknesses of the first coating layer and the second coating layer is 5-100 nm.

5. The hard carbon material according to claim 1 or 2, characterized in that: The porosity of the hard carbon material is 1% to 10%; And / or, the specific surface area of ​​the hard carbon material is 0.5 to 20 m 2 / g.

6. A method for preparing the hard carbon material according to any one of claims 1 to 5, characterized in that: include: Carbonizing the biomass raw material in a first inert atmosphere to obtain a hard carbon precursor; The hard carbon precursor is subjected to pore-forming treatment under the action of a pore-forming agent to obtain a pore-forming agent with a specific surface area of ​​300 to 900 m 2 / g of porous hard carbon precursor; After mixing the porous hard carbon precursor and a first coating agent, performing a first sintering treatment in a second inert atmosphere to obtain a coated porous hard carbon precursor, wherein the first coating agent includes a carbon source; After the coated porous hard carbon precursor and the second coating agent are mixed, a second sintering treatment is performed in a third inert atmosphere to obtain the hard carbon material, wherein the second coating agent includes a carbon-nitrogen source compound, and the carbon-nitrogen source compound includes an amine group and an alkyl group.

7. The method for preparing a hard carbon material according to claim 6, characterized in that: The biomass raw material includes one or more of glucose, sucrose, starch, coconut shell, walnut shell, hazelnut shell, and wood; And / or, in the process of carbonizing the biomass raw material to obtain the hard carbon precursor, the carbonization temperature is 300-800° C., the carbonization time is 1-10 hours, and the heating rate is 0.5-3° C. / min; And / or, the process of carbonizing the biomass raw material to obtain the hard carbon precursor further comprises: crushing and sieving the biomass raw material after carbonizing to obtain the hard carbon precursor with a mesh size of 300 to 500 meshes; And / or, the pore-forming agent includes a physical pore-forming agent, the physical pore-forming agent includes water vapor and / or carbon dioxide, and the temperature of the pore-forming treatment is 650-950° C.; And / or, the pore-forming agent includes a chemical pore-forming agent, the chemical pore-forming agent includes one or more of potassium hydroxide, sodium hydroxide, zinc chloride, and phosphoric acid, and the temperature of the pore-forming treatment is 500-900°C.

8. The method for preparing a hard carbon material according to claim 6 or 7, characterized in that: The carbon source includes asphalt and / or resin; And / or, the temperature of the first sintering treatment is 1100-1500° C., the holding time is 1-8 hours, and the heating rate is 0.5-3° C. / min; And / or, the temperature of the second sintering treatment is 700-950° C.; And / or, the carbon and nitrogen source compound further includes a carboxyl group, and the carbon and nitrogen source compound includes one or more of isoleucine, leucine, alanine, glycine, proline, valine, tyrosine, phenylalanine, tryptophan, serine, threonine, cysteine, asparagine, glutamine, aspartic acid, glutamic acid, lysine, and arginine; And / or, during the second sintering process, the heating rate is 0.5-3°C / min and the holding time is 2-6h.

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode active material layer, and the negative electrode active material layer comprises the hard carbon material according to any one of claims 1 to 5 or the hard carbon material prepared according to the method for preparing the hard carbon material according to any one of claims 6 to 8.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Hard carbon negative electrode material with multilayer core-shell structure and preparation method and application thereof

    CN113328067A

  • Negative electrode material and preparation method thereof, battery negative electrode and lithium ion battery

    CN113422030A

  • Negative electrode material and preparation method thereof, negative electrode plate and secondary battery

    CN116154129A

  • Hard carbon negative electrode material, preparation method thereof, negative electrode plate and application of negative electrode plate

    CN116632210A

  • Negative electrode material and preparation method thereof, negative electrode plate and secondary battery

    CN116960290A

Cited By

  • Hard carbon material, and preparation method therefor and use thereof

    WO2026166246A1